Genetic Architecture of Nitrogen-Deficiency Tolerance in Wheat Seedlings Based on a Nested Association Mapping (NAM) Population - Ren, Deqiang; Fang, Xiaojian; Jiang, Peng; Zhang, Guangxu; Hu, Junmei; Wang, Xiaoqian; Meng, Qing; Cui, Weian; Lan, Shengjie; Ma, Xin; Wang, Hongwei; Kong, Lingrang (Frontiers in Plant Science, 2018)
Genetic divergence for nitrogen utilization in germplasms is important in wheat breeding programs, especially for low nitrogen input management. In this study, a nested association mapping (NAM) population, derived from “Yanzhan 1” (a Chinese domesticated cultivar) crossed with “Hussar” (a British domesticated cultivar) and another three semi-wild wheat varieties, namely, “Cayazheda 29” (Triticum aestivum ssp. tibetanum Shao), “Yunnan” (T. aestivum ssp. yunnanense King), and “Yutian” (T. aestivum petropavloski Udats et Migusch), was used to detect quantitative trait loci (QTLs) for nitrogen utilization at the seedling stage. An integrated genetic map was constructed using 2,059 single nucleotide polymorphism (SNP) markers from a 90 K SNP chip, with a total coverage of 2,355.75 cM and an average marker spacing of 1.13 cM. A total of 67 QTLs for RDW (root dry weight), SDW (shoot dry weight), TDW (total dry weight), and RSDW (root to shoot ratio) were identified under normal nitrogen conditions (N+) and nitrogen deficient conditions (N−). Twenty-three of these QTLs were only detected under N− conditions. Moreover, 23 favorable QTLs were identified in the domesticated cultivar Yanzhan 1, 15 of which were detected under N+ conditions, while only four were detected under N− conditions. In contrast, the semi-wild cultivars contributed more favorable N−−specific QTLs (eight from Cayazheda 29; nine from Yunnan), which could be further explored for breeding cultivars adapted to nitrogen-deficient conditions. In particular, QRSDW-5A.1 from YN should be further evaluated using high-resolution mapping.